Ranking for cognitive salience of events and coding them into a sentence format (Categories and Units in Language and Linguistics, 2020)
This article discusses the use of different syntactic options in the construal of events.1 The examples selected for presentation and analysis come from a study by Badio (2014). This work understood construal to be non-linguistic, mental or conceptual, i.e. related to thought, whereas the term coding was reserved for the use of form to signal aspects of a conceptualisation. The present work focuses on demonstrating that if they are prominent, events tend to be coded with finite verb forms (of the superordinate) clause, followed by participial and infinitive constructions. The former contain the full processual profiles when they are used to relate the main participants, the subject and object. Infinitives and participles tend to be less cognitively salient, whereas nominalisations and other nonverbal options background the processual profile of an event. As a consequence, events coded with them are less salient within a clause or a sentence.